(untitled) (American Journal of Agricultural Science, Engineering, and Technology, 2023)
The landslide disaster, feeble geology, rapid deforestation, poor drainage system, and increase in mechanical strain have weakened the Krishna Bhir slope, Prithvi Highway, Dhading, Nepal. The objective of this article was to study the problems associated with bioengineering implementation in hill road construction with recommendations. For primary research, a map study, field observation, in-depth interview, focus group discussion, and questionnaire survey were used as an instrument for the field study. Published reports, papers, a thesis, database, manuals, and field observation were also reviewed. The landslide caused loss of property, ill effects on lifestyle, disturbance in the movement of goods and services, loss of availability of water due to damage to the water supply system, damage to the sewage disposal system, etc. During the construction period using the bioengineering technique, the major problem occurred during the installation of the bioengineered system (RII = 0.791), lack of training during construction (RII = 0.839), unavailability of space (RII = 0.817), inadequate supply of appropriate instruments (RII = 0.821) and improper selection of vegetation types (RII=0.839). The major problems were also seen during site monitoring and evaluation (RII= 0.853). Proper selection of plant species (RII=0.936) before implementation of the bioengineering technique is needed at hill roads, but the high installation costs (RII=0.841) could be the major limitation. Bioengineering application has a bright future if proper actions are taken in time. Solutions need to be formulated and implemented by understanding the major limitations of bioengineering techniques.